Smart Card basierte Berechnung einer Gruppensignatur als Teil einer biometrischen Authentisierung - Postler, Tim
Keywords: Diplomarbeit

Extraordinary Stories of the Ordinary Use of Media - Bartz, Christina (Media, Culture, and Mediality. New Insights into the Current State of Research)

Hochschulpolitische Herausforderungen anstatt studentischer Aufbruchstimmung - Bartz, Christina (Zeitschrift für Kulturwissenschaften)

Amok: Muster und Genealogie einer publizistischen Debatte von 1964 bis heute - Bartz, Christina (LiLi. Zeitschrift für Literaturwissenschaft und Linguistik H. 157)

Zu: Christian Morgner: Weltereignisse und Massenmedien. Studien zu John F. Kennedy, Lady Diana und die Titanic. Bielefeld 2009 - Bartz, Christina (H-Soz-U-Kult (15.10.10))

Barbara Korte / Sylvia Paletschek (Hrsg.): History Goes Pop. Zur Repräsentation von Geschichte in populären Medien und Genres (= Historische Lebenswelten in populären Wissenskulturen / History in Popular Cultures 1). Bielefeld 2009 - Hartung, Olaf (H-Soz-Kult)

Rezension von: Susanne Popp / Bernd Schönemann (Hrsg.): Historische Kompetenzen und Museen (= Schriften zur Geschichtsdidaktik, Bd. 25) Idstein 2009 - Hartung, Olaf (Zeitschrift für Geschichtsdidaktik)

Lernen und Kultur. Kulturwissenschaftliche Perspektiven in den Bildungswissenschaften

O. Auge u. a. (Hgg.): Fürsten an der Zeitenwende zwischen Gruppenbild und Individualität. Formen fürstlicher Selbstdarstellung und ihre Rezeption (1450–1550). Ostfildern 2009 - Moritz, Tilman (H-Soz-Kult)

R. Dauser u. a. (Hgg.): Wissen im Netz. Botanik und Pflanzentransfer in Korrespondenznetzen des 18. Jahrhunderts. Berlin 2008 - Moritz, Tilman (H-Soz-Kult)

Ohne Titel (2008) - Schulze, Max (Parcours Interdit)

Unmarked State - Schulze, Max

Teil 4 - Schulze, Max (AbaB. Eine kontinuierliche Ausstellungsreihe)

Video-Visionen. Die Mobilisierung eines AV-Mediums - Bartz, Christina (Portable Media)

Zum europäischen Deutsch: Formen und Funktionen des Fremdwortgebrauchs bei Elisabeth von Heyking (1861–1925) und Harry Kessler (1868–1937) - Schuster, Britt-Marie (Bausteine zu einer Geschichte des weiblichen Sprachgebrauchs. IX. Zum Sprachgebrauch in Texten von Frauenhand im Kontext des allgemeinen Sprachgebrauchs. Internationale Fachtagung. Magdeburg 06.–08.09.2010)
Keywords: Textsemantik

Gibt es eine Zeitungssyntax? Überlegungen und Befunde zum Verhältnis von syntaktischer Gestaltung und Textkonstitution in historischen Pressetexten - Schuster, Britt-Marie (Historische Textgrammatik und Historische Syntax des Deutschen)
Keywords: Textgrammatik

"Aber was rede ich?" – Sprachgebrauch und Ethik am Beispiel des Essays - Schuster, Britt-Marie (Sprache und Literatur in Wissenschaft und Unterricht 41. Sonderheft: Literatur und Ethik)
Keywords: Sprachliche Formelhaftigkeit/-Musterhaftigkeit

Preference-Based Multi-Objective Particle Swarm Optimization Using Desirabilities - Mostaghim, Sanaz; Trautmann, Heike; Mersmann, Olaf (Parallel Problem Solving from Nature, PPSN XI)
The integration of experts’ preferences is an important aspect in multi-objective optimization. Usually, one out of a set of Pareto optimal solutions has to be chosen based on expert knowledge. A combination of multi-objective particle swarm optimization (MOPSO) with the desirability concept is introduced to efficiently focus on desired and relevant regions of the true Pareto front of the optimization problem which facilitates the solution selection process. Desirability functions of the objectives are optimized, and the desirability index is used for selecting the global best particle in each iteration. The resulting MOPSO variant DF-MOPSO in most cases exclusively generates solutions in the desired area of the Pareto front. Approximations of the whole Pareto front result in cases of misspecified desired regions.

Benchmarking Evolutionary Algorithms: Towards Exploratory Landscape Analysis - Mersmann, Olaf; Preuss, Mike; Trautmann, Heike (Proceedings of the 11th International Conference on Parallel Problem Solving from Nature: Part I)
We present methods to answer two basic questions that arise when benchmarking optimization algorithms. The first one is: which algorithm is the ’best’ one? and the second one: which algorithm should I use for my real world problem? Both are connected and neither is easy to answer. We present methods which can be used to analyse the raw data of a benchmark experiment and derive some insight regarding the answers to these questions. We employ the presented methods to analyse the BBOB’09 benchmark results and present some initial findings.
Keywords: benchmarking; multidimensional scaling; consensus ranking; evolutionary optimization; BBOB test set

On the Distribution of EMOA Hypervolumes - Mersmann, O; Trautmann, Heike; Naujoks, B; Weihs, C (Learning and Intelligent Optimization, 4$^th$ International Conference, LION 4, Venice, Italy)
We present methods to answer two basic questions that arise when benchmarking optimization algorithms. The first one is: which algorithm is the 'best' one? and the second one: which algorithm should I use for my real world problem? Both are connected and neither is easy to answer. We present methods which can be used to analyse the raw data of a benchmark experiment and derive some insight regarding the answers to these questions. We employ the presented methods to analyse the BBOB'09 benchmark results and present some initial findings.

Benchmarking evolutionary multiobjective optimization algorithms - Mersmann, Olaf; Trautmann, Heike; Naujoks, Boris; Weihs, Claus (IEEE Congress on Evolutionary Computation)
Choosing and tuning an optimization procedure for a given class of nonlinear optimization problems is not an easy task. One way to proceed is to consider this as a tournament, where each procedure will compete in different ‘disciplines’. Here, disciplines could either be different functions, which we want to optimize, or specific performance measures of the optimization procedure. We would then be interested in the algorithm that performs best in a majority of cases or whose average performance is maximal. We will focus on evolutionary multiobjective optimization algorithms (EMOA), and will present a novel approach to the design and analysis of evolutionary multiobjective benchmark experiments based on similar work from the context of machine learning. We focus on deriving a consensus among several benchmarks over different test problems and illustrate the methodology by reanalyzing the results of the CEC 2007 EMOA competition.

Sequential Parameter Optimisation for Multi-Objective Evolutionary Optimisation of Additive Layer Manufacturing - Ding, J; Wessing, S; Trautmann, Heike; Mehnen, J; Naujoks, B (Proceedings of the 7$^th$ CIRP International Seminar on Intelligent Computation in Manufacturing Engineering (CIRP ICME ’10))

New Uncertainty Handling Strategies in Multi-objective Evolutionary Optimization - Voß, Thomas; Trautmann, Heike; Igel, Christian (Parallel Problem Solving from Nature, PPSN XI)
Since many real-world optimization problems are noisy, vector optimization algorithms that can cope with noise and uncertainty are required. We propose new, robust selection strategies for evolutionary multi-objective optimization in the presence of noise. We apply new measures of uncertainty for estimating the recently introduced Pareto-dominance for uncertain and noisy environments (PDU). The first measure is the inter-quartile range of the outcomes of repeated function evaluations. The second is based on axis-aligned bounding boxes around the upper and lower quantiles of the sampled fitness values in objective space. Experiments on real and artificial problems show promising results.

Integration of Preferences in Hypervolume-Based Multiobjective Evolutionary Algorithms by Means of Desirability Functions - Wagner, Tobias; Trautmann, Heike (IEEE Transactions on Evolutionary Computation)
In this paper, a concept for efficiently approximating the practically relevant regions of the Pareto front (PF) is introduced. Instead of the original objectives, desirability functions (DFs) of the objectives are optimized, which express the preferences of the decision maker. The original problem formulation and the optimization algorithm do not have to be modified. DFs map an objective to the domain [0, 1] and nonlinearly increase with better objective quality. By means of this mapping, values of different objectives and units become comparable. A biased distribution of the solutions in the PF approximation based on different scalings of the objectives is prevented. Thus, we propose the integration of DFs into the S-metric selection evolutionary multiobjective algorithm. The transformation ensures the meaning of the hypervolumes internally computed. Furthermore, it is shown that the reference point for the hypervolume calculation can be set intuitively. The approach is analyzed using standard test problems. Moreover, a practical validation by means of the optimization of a turning process is performed.

Work roll cooling system design optimisation in presence of uncertainty and constrains - Azene, Y.T.; Roy, R.; Farrugia, D.; Onisa, C.; Mehnen, J.; Trautmann, Heike (CIRP Journal of Manufacturing Science and Technology)
The paper presents a framework to optimise the design of work roll based on the cooling performance. The framework develops meta-models from a set of finite element analyses (FEA) of the roll cooling. A design of experiment technique is used to identify the FEA runs. The research also identifies sources of uncertainties in the design process. A robust evolutionary multi-objective evaluation technique is applied to the design optimisation in constrained problems with real life uncertainty. The approach handles uncertainties associated both with design variables and fitness functions. Constraints violation within the neighbourhood of a design is considered as part of a measurement for degree of feasibility and robustness of a solution.
Keywords: Roll cooling design; Uncertainty; Design optimisation; Multi-objective optimisation; Constraint in design

Online convergence detection for evolutionary multi-objective algorithms revisited - Wagner, Tobias; Trautmann, Heike (IEEE Congress on Evolutionary Computation)
The design and application of termination criteria has become an important aspect in evolutionary multi-objective optimization. Online convergence detection (OCD) determines when further generations are no longer promising based on statistical tests on a set of performance indicators. The behavior of OCD mainly depends on two parameters, the number of preceding generations considered in the statistical tests and the desired variance limit. In this paper, guidelines for selecting appropriate combinations of these parameters are empirically derived based on design-of-experiment methods. Furthermore, a variant of OCD is introduced which directly operates on the hypervolume indicator - the internal measure of the SMS-EMOA. This allows a separated analysis of the variance criterion and reduces the complexity of OCD. Based on the experimental design, a systematic comparison with the classical OCD approach is performed and differences between the appropriate parameterizations of both variants are highlighted.

Online Diarization of Streaming Audio-Visual Data for Smart Environments - Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (IEEE Journal of Selected Topics in Signal Processing)
For an environment to be perceived as being smart, contextual information has to be gathered to adapt the system's behavior and its interface towards the user. Being a rich source of context information speech can be acquired unobtrusively by microphone arrays and then processed to extract information about the user and his environment. In this paper, a system for joint temporal segmentation, speaker localization, and identification is presented, which is supported by face identification from video data obtained from a steerable camera. Special attention is paid to latency aspects and online processing capabilities, as they are important for the application under investigation, namely ambient communication. It describes the vision of terminal-less, session-less and multi-modal telecommunication with remote partners, where the user can move freely within his home while the communication follows him. The speaker diarization serves as a context source, which has been integrated in a service-oriented middleware architecture and provided to the application to select the most appropriate I/O device and to steer the camera towards the speaker during ambient communication.
Keywords: audio streaming; audio visual data streaming; context information speech; face identification; face recognition; image segmentation; middleware; multimodal telecommunication; online diarization; service oriented middleware architecture; sessionless telecommunication; software architecture; speaker identification; speaker localization; speaker recognition; steerable camera; telecommunication computing; temporal segmentation; terminal-less telecommunication; video streaming

Räumungsszenarien bei Großveranstaltungen: Modellierung einer Datenbasis füur Planung und Forschung - Schneider, Steffen; Pottebaum, Jens; Becker, Tobias; Koch, Rainer (Informatik 2010: Service Science - Neue Perspektiven für die Informatik, Beiträge der 40. Jahrestagung der Gesellschaft für Informatik e.V. (GI), Band 2, 27.09. - 1.10.2010, Leipzig, Deutschland)
Keywords: Ver{\

Design and modeling of a domain ontology for fire protection - Pottebaum, Jens; Japs, Anna Maria; Prödel, Stephan; Koch, Rainer (ISCRAM 2010 -- 7th International Conference on Information Systems for Crisis Response and Management)
Keywords: Command and control process; Command and control systems; Design and modeling; Domain ontologies; Emergency response; Fire extinguishers; Fire protection; Heterogeneous domains; Information analysis; Information sharing; Information systems; Interoperability; Ontology language; Semantic technologies; Semantic Web; Semantics

Historisches Lernen und (Schreib-)Kultur. Zur Bedeutung einer ‚Kulturtechnik‘ für das Geschichtslernen - Hartung, Olaf (Lernen und Kultur: Kulturwissenschaftliche Perspektiven in den Bildungswissenschaften)

Geschichte schreiben und lernen. Eine empirische Studie - Hartung, Olaf (Sprache und Geschichte)

Kleine deutsche Museumsgeschichte: von der Aufklärung bis zum frühen 20. Jahrhundert - Hartung, Olaf

Tarnversuch im Atelier / Flashmob 1-4 - Schulze, Max (smax #1 Magazine)

Nervöses Wohnen - Schulze, Max
Katalog zur Ausstellung vom 10.09 – 09.10.2011 in der Galerie Börgmann, Krefeld

Radar R2120 - Schulze, Max
Katalog zur Ausstellung vom 13. - 24.10.2013 in The Store Front, Popps Packing, Hamtramck, Detroit, USA

Poetische Ordnungen. Zur Erzählprosa des deutschen Realismus - Gretz, Daniela (Jahrbuch der Raabe-Gesellschaft)

Das Subjekt als moralische Person. Zu Husserls späten Reflexionen bezüglich des Personenbegriffs - Luft, Sebastian (Geist, Person, Gemeinschaft: Freiburger Beiträge zur Aktualität Husserls)
In this essay, I will attempt a systematic reconstruction of the general shape of Husserl’s late philosophy, insofar as it centers on the concept of personhood. The systematic concatenation of this and other themes in Husserl’s late work – the method of epoché and reduction, ethics, personhood, and teleology – has only recently begun to be explored in Husserl scholarship, and this article is a modest contribution to the further elucidation of their mutual relation-ship. One of the most striking results of this reconstructive analysis is Husserl’s final concept of “person“, which goes beyond the traditional distinctions, such as “heart“ and “mind“ or “reason“ and “emotion“. For Husserl to conceive of the subject as moral person implies, then, the demand to not only conduct oneself morally (in a novel sense of “moral”), but also to have an ethical view of the world as a world that bears meaning and harbors values despite its apparent absurdities.

Axel Dunker: Kontrapunktische Lektüren. Koloniale Strukturen in der deutschsprachigen Literatur des 19. Jahrhunderts - Gretz, Daniela (ZfdPh)

Tora

Perfekt II und Plusquamperfekt II. Zur historischen Kontinuität doppelter Perfektbildungen im Deutschen - Topalović, Elvira (Sprache in der Stadt. Akten der 25. Tagung des Internationalen Arbeitskreises Historische Stadtsprachenforschung. Luxemburg, 11.–13. Oktober 2007.)

Who Cares about the Music in Music Videos? Toward a Multiperspectival Pop Cultural Study of Music Videos. - Jacke, Christoph (Rewind, Play, Fast Forward. The Past, Present and Future of the Music Video.)

Poptheorie, Popkulturforschung und Literaturwissenschaft. - Jacke, Christoph; Goer, Charis; Greif, Stefan (Literaturwissenschaft interdisziplinär.)

Figurenkonzepte in der Popmusik. - Jacke, Christoph (Formen der Figur. Figurenkonzepte in Künsten und Medien.)

Mister Dazwischen. Ferry, das Forschungsobjekt: Warum nur beschäftigen sich Popwissenschaftler so gern mit Roxy Music? - Jacke, Christoph (Rolling Stone)

Pop und Erinnerung: Zu Anforderungen und Förderungen eines scheinbaren Widerspruchs. Vom populären Trend des Sammelns, Einordnens und Aufbewahrens. - Jacke, Christoph (kultur.macht.geschichte. - geschichte.macht.kultur. Kulturpolitik und kulturelles Gedächtnis. Dokumentation des Fünften Kulturpolitischen Bundeskongresses.)

Mainstreams und Minderheiten im Spannungsfeld von Kontingenz und Kontroverse. Erneute Erläuterungen zum Subkultur-Begriff. - Jacke, Christoph (inter-cool 3.0. Jugend Bild Medien. Ein Kompendium zur aktuellen Jugendkulturforschung.)

Sex - Popmusik - Medien. Literatursynopse und empirische Daten aus hochschuldidaktischer Projektarbeit. - Jacke, Christoph; Ahlers, Michael (Merz. Medien + Erziehung. Zeitschrift für Medienpädagogik.)

Zurück zum Beton. Pop in der Universität: Eine Paradoxieent- und -einfaltung. - Jacke, Christoph (Paderborner Universitätsreden)

Mehr als nur ein Fremdwort. Zum Stellenwert der Religion in Hans Magnus Enzensbergers lyrischem Spätwerk - Diedrich, Alena (Hans Magnus Enzensberger und die Ideengeschichte der Bundesrepublik. Mit einem Essay von Lars Gustafsson)

Polke für Alle! Zugänge zu den künstlerischen Arbeiten und Strategien von Sigmar Polke und seiner Kunst [= Studentisches Projekt im Rahmen einer "Didaktik der Kunstegschichte" an der Universität Paderborn]